UPGRADATION OF T.E.M.S ACADEMY DIGITAL LEARNING PLATFORM TO ENHANCE ADVANCED EDUCATION DURING COVID 19 - Pon Maa Kishan (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
T.E.M.S Academy is developed to enhance the digital learning mode during this Covid 19. T.E.M.S Academy mainly focusing on the lectures or courses related to the aeronautics and space science. Its been a month after the T.E.M.S academy is designed and developed. In this article, the tool upgradation, theme upgradation, plug-in upgradation of T.E.M.S academy is discussed. Also, during the Covid 19 the impact of T.E.M.S academy among the Indian aerospace enthusiastic students, faculty and scientists is discussed in the later part of the article. Mostly the paper covers technical updates and changes done in T.E.M.S academy and it is not covering the lecture analysis, feedback and responses.